Bahasa Inggris - Nabil, Mohammad Adib (Widya Komunika, 2025)
This study explores the transformation of question-and-answer dynamics as a catalyst for developing communicative competencies among Office Administration Education students. The "silent classroom" phenomenon has become a significant challenge in higher education, particularly in developing professional communication skills that are vital for graduates in the field of office administration. Through a descriptive-analytical qualitative approach, this study dissects the complexity of dialogical interactions in learning spaces and analyzes their impact on students' communication abilities. Data collection was conducted through interviews involving 15 student respondents. The data were analyzed through stages of reduction, presentation, and conclusion drawing with an interpretative-constructivist approach. The results show that structured and continuous question-and-answer activities serve as significant catalysts in building idea articulation, active listening skills, and students' communicative confidence. This research identifies three crucial factors that form an effective dialogical ecosystem: (1) a supportive psychological classroom atmosphere, (2) dialogue-centered teaching methodologies, and (3) students' mental frameworks in facing academic interactions. The findings suggest a pedagogical reorientation that places dialogue at the center of the learning experience to prepare graduates with communicative competencies that are vital needs in the professional world of office administration. The "voicing the silence" approach offered in this research provides an innovative conceptual framework for transforming communication dynamics in academic spaces while bridging the gap between graduate competencies and workplace demands.